Monitoring and Treatment of Juvenile Idiopathic Arthritis-associated Uveitis: Brazilian Evidence-based Practice Guidelines - Neves, L. M. (2021)
Purpose: To present a national guideline for ophthalmologic care and surveillance of juvenile idiopathic arthritis-associated uveitis (JIA-uveitis).Methods: Review article based on medical literature and the experience of an Expert Committee composed of members of the Brazilian Society of Pediatric Ophthalmology/Brazilian Council of Ophthalmology and the Brazilian Society of Pediatrics/Brazilian Society of Rheumatology. Studies with a high level of evidence were selected by searching the PubMed/Medline database. The final document was approved by the experts.Results: The main recommendations are that children/adolescents with JIA should undergo screening according to their risk factors. Ophthalmological checkups should also consider ocular inflammation and therapy. Topical glucocorticoids should be the first line of therapy, with systemic glucocorticoids acting as bridge treatments in severe uveitis. Methotrexate should be the first-line systemic therapy and anti-tumor necrosis factor (anti-TNF alpha) the second for uncontrolled uveitis.Conclusions: This evidence-based guideline for JIA-uveitis will be useful for both ophthalmology and rheumatology practice.